Current Status of Research Information Management in Peru - Melgar Sasieta, Hector Andrés (2019)
Nowadays, there is full consensus that the promotion of Science, Technology and Innovation has a positive impact on the economic growth of a country. In Peru, national and institutional STI decision-making is hindered by the lack of information on research activities. The National Council of Science, Technology and Technological Innovation (CONCYTEC) in Peru is increasingly aware of the value of embracing best practices in Research Information Management (RIM) and establishing an adequate national CRIS infrastructure, a project which has taken the name PeruCRIS. In order to assess a baseline status for RIM practices along with other research management needs, CONCYTEC visited 20 public universities, 23 private universities and 10 research institutes and promoted the participation of Peruvian institutions in a Global Survey on Research Information Management (RIM) Practices. Although only 6 institutions reported having a RIM system, more than half survey respondent institutions were in the process of exploring, acquiring or implementing one. Most RIM systems have being developed in-house, and no commercial CRIS product was reported. Interoperability of existing RIMs is very limited with internal systems. No interoperability with external systems or support for persistent identifiers was reported. Institutions expressed very positive expectations regarding the role of CONCYTEC in the establishment of a national CRIS infrastructure in Peru.